EFFECTIVE INNOVATIVE METHODS OF TEACHING PSYCHOLOGY - Marufjanova, Raykhona (MMIT Proceedings, 2023)
One of the actual tasks in the methodology of teaching psychology is the transition to an innovative path of development. To implement innovative activities, specialists are needed who have the methods, means and forms of managing innovative processes. This article is devoted to the consideration of innovative technologies in psychology in higher educational institutions.